PENGARUH MODEL PEMBELAJARAN RELATING, EXPERIENCING, APPLYING, COOPERATING, TRANSFERRING TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS XI SMAN 1 SULIKI - Yahya, Muthia Alayda (Jurnal Edukasi dan Penelitian Matematika, 2024)
Class XI pupils at SMA Negeri 1 Suliki still have room to grow academically. The learning model that is employed during the learning process is one of the aspects that impact the final product of the learning. The REACT Learning Model—which stands for "relating, experiencing, applying, cooperating, and transferring"—could be one approach to making it better. This study aims to answer the question, "Do students in class XI at SMA Negeri 1 Suliki perform better in mathematics when they use the REACT learning model compared to when they use conventional learning?" This study used a quasi-experimental design with a control group that was only given a post-test rather than an equal one. Students in grades XI F2 and XI F3 at SMA Negeri 1 Suliki made up the study's population. The study's instrument was a description-based last assessment of learning outcomes. Class XI students at SMA Negeri 1 Suliki who used traditional learning models for mathematics performed worse than those who used Learning (REACT).Keywords– Mathematics Learning Outcomes, REACT Learning Model, Conventional Learning Model